Study of the Use of the Parasarg in Hindi and Prepositions in Thai - Kaewruang, Saman; Sinak, Sanit (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 11 No 1 (2019): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2020)
Language is a human medium used to communicate understanding between each other. The choice of words in the language to be compiled into a proper and proper manner will be beneficial for the purpose and success of the communication process. And the word connection is an important part. Because it is a part of the meaning of each word in a related sentence is properly harmonious. Hindi uses the word "Parasarg" to connect words in sentences and place them after the nouns and pronouns which are different from the prepositions in Thai which are placed in front of nouns, pronouns and adverbs.